The importance of morphometric parameters in differentiating benign/reactive urothelial cells from low-grade urothelial carcinoma: computer-assisted study on urine specimens - Musayev, J.; Metilli, N.; Sholan, R.; Hasanov, A.; Damirli, A.; Bakhshaliyeva, K. (Морфологія / Morphologia / Morfologìâ, 2021)
Background. Urine cytology is deemed a sensitive method in detection of high-grade urothelial carcinoma. In contrast, detection of low-grade urothelial carcinoma (LGUC) and its differentiation from reactive lesions is difficult with urinary cytology. Objective. Our study aims to determine the effectiveness of morphometric parameters in differentiating reactive urothelial cells from LGUC by cytological examination of urine specimens. Methods. Voided urine samples were used for the study, while the cases were randomized into two groups: those diagnosed with LGUC (first group; N=10) and those which were not diagnosed with LGUC (second group; N=10). The morphometric parameters of major nuclear diameter (MaND), minor nuclear diameter (MiND), mean nuclear area (MNA), cell diameter (CD), mean cell area (MCA), as well as MaND/CD, MiND/CD, MiND/MaND and MNA/MCA ratios were measured on 100 urothelial cells for each case through ScopeImage® 9.0 software. Results. A statistically significant difference was found between the mean values of MiND/CD (p=0.017) and MNA/MCA (p=0.002) ratios of groups. The mean value of both parameters in the first group constituted 0.2 and higher, and below 0.2 in the second group. Conclusion. The ratios of MiND/CD and MNA/MCA in urothelial cells proved significantly higher in patients with LGUC than benign/reactive cases. The reliability of these findings in differentiating LGUC from benign/reactive lesions needs to be verified through studies examining a large number of cases. These parameters can be assessed much faster through a special software enabling an automatic measurement and thus can be used in routine cytological examination.